2011
DOI: 10.3892/ijmm.2011.807
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of α-MSH and IBMX-induced melanogenesis by cordycepin via inhibition of CREB and MITF, and activation of PI3K/Akt and ERK-dependent mechanisms

Abstract: Abstract. Cordycepin has been a traditional medicine in China and Korea for centuries. This study explored the inhibitory effect of cordycepin on melanogenesis and the relative molecular mechanisms. Cordycepin inhibited melanin synthesis-related enzymes, such as tyrosinase, tyrosinaserelated protein-1 (TRP1) and tyrosinase-related protein-2 (TRP2). α-MSH and IBMX were reported as melanin synthesis enhancers. Both of them could increase intracellular melanin synthesis by activation of the microphthalmia-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…Melanogenesis is modulated by several factors, including UV irradiation, alpha‐melanocyte‐stimulating hormone ( α ‐MSH) 7, forskolin, stem cell factor (SCF) 8, wnt‐3a 9 and isobutylmethylxanthine (IBMX) 10, within intracellular melanosomes in the melanocytes 11. Stimulation of the melanocortin 1 receptor (MC1R) by α ‐MSH activates adenyl cyclase through G protein signalling, which subsequently increases cyclic adenosine monophosphate (cAMP) production.…”
Section: Introductionmentioning
confidence: 99%
“…Melanogenesis is modulated by several factors, including UV irradiation, alpha‐melanocyte‐stimulating hormone ( α ‐MSH) 7, forskolin, stem cell factor (SCF) 8, wnt‐3a 9 and isobutylmethylxanthine (IBMX) 10, within intracellular melanosomes in the melanocytes 11. Stimulation of the melanocortin 1 receptor (MC1R) by α ‐MSH activates adenyl cyclase through G protein signalling, which subsequently increases cyclic adenosine monophosphate (cAMP) production.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies suggest that Akt inhibition is related to decreased cell growth and reduced cancer cell migration ( Sarkar and Li, 2004 ), suggesting that Akt inhibition may be an attractive approach for preventing or treating human malignancies ( Hill and Hemmings, 2002 ; Sarkar and Li, 2004 ). However, Akt activation has been implicated in cell death mediated by natural products in B16F10 murine melanoma and U373 glioblastoma cell lines ( Jin et al ., 2012 ). Thus, the roles of Akt activation and cell cycle regulation in the inhibition of cancer cell proliferation require further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…As tyrosinase is a critical determinant of melanin synthesis in melanocytes [41], we examined the effect of Mc-ME on tyrosinase activity and showed that Mc-ME dose-dependently suppressed tyrosinase activity in B16F10 cells (Figure 4(b)). We next examined the effect of Mc-ME on the production of melanin from melanocytes by measuring melanin content and secretion in B16F10 cells stimulated with α -MSH, which induces melanogenesis by activating melanogenesis-specific transcription factor and enzymes associated with melanin synthesis [42, 43]. As expected, Mc-ME effectively suppressed the production and secretion of melanin from melanocytes induced by α -MSH (Figures 4(c) and 4(d)).…”
Section: Discussionmentioning
confidence: 77%